Salud mental: Experiencias significativas desde la práctica clínica en el Centro de Atención Psicológica (CAP) Sede Armenia (Hilo Analítico, 2022)
This article refers to mental health: significant experiences from clinical practice in the psychological care center (CAP), which aims to describe the experiences from clinical practice in the psychological care center, through the process of teleorientation. Likewise, the methodology used was descriptive, the information gathering techniques used were the semi-structured interview, the clinical history and the field diary. The results obtained were through the reason for consultation, which showed difficulties in mental health such as stress, difficulty managing emotions, relationship problems, social anxiety, depression and panic. Therefore, it was concluded that the accompaniment through teleorientation has been satisfactory, where the therapeutic objectives have been successfully fulfilled, likewise the intervened patients have presented positive changes in the different spheres of their lives, based on the tools provided, necessary to be able to cope with the problems that afflicted them. Thus, as practitioners in the area of ​​clinical psychology, the objectives proposed at the beginning of the different sessions assigned to the patients were achieved.Keywords: Mental health, clinical area, pandemic, care, intervention.
Keywords: Mental health, clinical area, pandemic, care, intervention.